The Effectiveness of Internalizing the Value of Local Wisdom by Using the Nampe Model in Improving the Mitigation Ability of Covid-19 in Elementary School Students - Muhammad Hanif (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to test the effectiveness of internalizing the value of local wisdom with the Nampe Model in increasing the Covid-19 mitigation ability in IV grade elementary school students. This research used quantitative research in Sodong Hamlet and SDN Gelankulon IV for eight months. Then, the data collection technique used was authentic assessment techniques on affective, cognitive, and psychomotor aspects. The data obtained were analyzed by descriptive statistics using SPSS. The results show that the people in Dusun Sodong value local wisdom in mitigating Covid-19. These values include religious, moral, tolerance, cooperation, caring, and responsibility. The value of this local wisdom has the potential to be a source of social science studies. So, SDN Gelangkulon teachers need to internalise this study, especially for the IV grade student. The goal of the implementation is that the students can increase their abilities to mitigate Covid-19. Then, it also follows the core and basic competencies set by the curriculum. Teachers in internalizing the value of local wisdom of the Sodong Hamlet community use the Nampe Model. The average value of students’ abilities in mitigating Covid-19 using the Nampe Model = 78.67, the Indoctrination Model = 68.430 and the Open Model = 67.14. These results show that using the Nampe Model results in better and more effective results than the indoctrination model and the open model with a significance of 0.000 0.05. While the use of the indoctrination model and the open model almost have no difference because the significance is 0.570 0.05. The internalization of values with the Nampe Model makes students grow their well awareness to carry out Covid-19 mitigation.